Akselarasi Program Inovasi Pendidikan Dan Monitoring Evaluasi Dalam Inovasi Pendidikan - Trisnawati, Nadia; Ismail, Fajri; Afgani, Muhammad Win (Jurnal Ilmiah Wahana Pendidikan, 2025)
Acceleration of educational innovation programs is a strategy to improve the quality of learning and accelerate the achievement of student competencies. This acceleration program is intended for students with special intelligence and talents, allowing them to complete their education in a shorter time compared to the regular path. In addition to acceleration, monitoring and evaluation (monev) are important factors in the success of educational innovation. This study uses a literature review method by analyzing various literature related to the acceleration of educational innovation and monev in the education system in Indonesia. The results of the study show that the acceleration of educational innovation programs supported by a continuous monitoring and evaluation system can improve the quality of education, provide a more adaptive learning experience for students, and produce graduates who are better prepared to face global challenges.